Hubungan antara Sikap Kerja terhadap Keluhan Musculoskeletal Disorders pada Pekerja Angkat Angkut Penyuplai Minimarket Lely - Nyoman Mery Arya Meiantini; Ni Wayan Rusni; Ni Wayan Winianti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Musculoskeletal Disorders (MSDs) are a collection of conditions that affect musculoskeletal system at the extreme points of the body in the upper and lower extremities. Some of the main factors that trigger these complaints are overstretching the muscles, repetitive movements, and unnatural work attitudes. Lifting workers generally work using their bodies as a means of transportation. In addition, this work requires a large amount of energy, so workers are often more concerned with getting the job done quickly without considering work attitudes while working. The primary objective of this research is to examine how the work ethics of lift workers at Lely Minimarket are linked to the occurrence of musculoskeletal complaints. The research employed a cross-sectional observational analytic method. This study utilized a total sampling technique. Data analysis was carried out univariately and bivariate with the SPSS 25 version. According to the results that highest proportion of lift workers were male, in the early adult age category, and worked 7-12 hours per day. Most of the workers (72.5%) have a normal body mass index and 64% have a working period of <5 years. Based on the result, the most respondents (55%) had a very high risk work attitude in the form of a bent back, upper arms raised and away from the body, and neck flexion-extension. MSDs complaints experienced by the majority of respondents were in the high category, especially in the area of the waist (92.5%), back (87.5%) and upper arms (85%). The Spearman Correlation test analysis yielded results that indicated a significant correlation between work attitude and musculoskeletal complaints (r = 0.600, p <0.05) in lift workers supplying Lely Denpasar Minimarket. Based on the results acquired, it is important to improve the work attitude of workers as soon as possible so that there is a decrease in the level of MSD complaints, in the form of providing lifting aids aimed at business owners.